1978
DOI: 10.1177/070674377802300709
|View full text |Cite
|
Sign up to set email alerts
|

The Authoritarian Family and its Adolescents

Abstract: Authoritarian Families possess characteristics similar to those of the Authoritarian Personality. They are power oriented, tend to have dichotomous conceptions, have emotional and intellectual rigidity and submit easily to authoritarian forces. The adolescents in such families are deprived of their basic needs for stability, flexibility and guidance. Consequently they feel frustrated and angry. Their anger manifests itself in various forms. A large percentage of these adolescents adopt their parents' attitudes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…CoH addresses all this issues and in doing so, complements both PTSD and TRC approaches and opens the door for an empirical study of psychosocial and moral/spiritual recovery from large-scale violence-induced conditions. In my analysis of this rather complex process, I will draw from my previous work on the nature and dynamics of process of psychological health at individual, group, and community levels with special reference to the issues of violence, peace, and the processes of psychosocial healing (Danesh 1969(Danesh , 1977(Danesh , 1978a(Danesh , 1978b(Danesh , 1979(Danesh , 1986(Danesh , 1995. The following is a brief summary.…”
Section: What Is a Culture Of Healing?mentioning
confidence: 99%
“…CoH addresses all this issues and in doing so, complements both PTSD and TRC approaches and opens the door for an empirical study of psychosocial and moral/spiritual recovery from large-scale violence-induced conditions. In my analysis of this rather complex process, I will draw from my previous work on the nature and dynamics of process of psychological health at individual, group, and community levels with special reference to the issues of violence, peace, and the processes of psychosocial healing (Danesh 1969(Danesh , 1977(Danesh , 1978a(Danesh , 1978b(Danesh , 1979(Danesh , 1986(Danesh , 1995. The following is a brief summary.…”
Section: What Is a Culture Of Healing?mentioning
confidence: 99%
“…This is the basic trust of which Erik Erikson speaks. 47 Another source of trust is knowledge. Ignorance tends to create fear and anxiety, while knowledge reduces fear and increases our ability to trust and have faith.…”
Section: The Acquisition and Development Of Faithmentioning
confidence: 99%
“…Further, it found that achievement training practices are more frequent in democratic than in autocractic families. In fact, studies indicate that adolescents of authoritarian families show great difficulty even in dealing with the ordinary demands of their lives (Danesh, 1978).…”
Section: Status In the Familymentioning
confidence: 99%
“…How an individual comes out of this phase of storm and stress also depends on his family socialization during this period (Danesh, 1978;Mahdeva, 1977;Shukla, 1976Shukla, , 1978. Studies have indicated that the period of adolescence is also equally important for the development of achievement oriented values and behavior (Allen, 1978;Dolan, 1978;Rehberg, et al, 1970).…”
mentioning
confidence: 99%